Downregulation of CISD2 Has Prognostic Value in Non-Small Cell Lung Cancer and Inhibits the Tumorigenesis by Inducing Mitochondrial Dysfunction - Shao, Fangchun; Li, Yanchun; Hu, Wanye; Yu, Jiaqi; Wu, HengYu; Ying, Kejing; Xia, Jun; Du, Jing (Frontiers in Oncology, 2021)
CISD2, a member of NEET proteins, which coordinated 2Fe-2S clusters through its CDGSH domain, is critical for normal development and iron homeostasis. CISD2 has demonstrated to play an important role in Fe-S clusters transfer and promote cancer proliferation. However, its specific role in the development of NSCLC (Non-small cell lung cancer) is still unclear. Bioinformatics of pan-cancer analysis from TCGA shows that CISD2 has an aberrant expression in most types of human cancers. And CISD2 expression associates with a higher hazard ratio, exhibits significantly poorer overall survival in LUAD (Lung adenocarcinoma), UVM (Uveal Melanoma), HNSC (Head and Neck squamous cell carcinoma), LGG (Brain Lower Grade Glioma), KICH (Kidney Chromophobe) and LIHC (Liver hepatocellular carcinoma). Further study discovers that CISD2 is highly expressed in LUAD and LUSC, which is associated with clinical pathological stages. In addition, survival data collected from GSE31210 and GSE13213, two datasets from GEO, also confirmes that high CISD2 expression was associated with unfavorable survival in patients with LUAD. Cell-based assay indicated that the knockdown of CISD2 inhibited the abilities of proliferation, invasion and migration in A549 cells. Additionally, CISD2 knockdown accelerated the accumulation of cellular and mitochondrial reactive oxygen species (ROS), destroyed the mitochondrial morphology and function. Moreover, CISD2 inhibition activation the process of iron starvation response, thus accelerating iron accumulation in A549 cells. Pretreatment of DFO, the iron chelator, could block mitochondrial dysfunction in CISD2 knockdown cells. Collectively, the present work provides novel insights into the regulatory role of CISD2 in NSCLC and presents a potential target to improve antitumor activity base on oxidative stress.